2020
DOI: 10.3389/fnins.2020.00689
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Disturbances and Sleep Disordered Breathing Impair Cognitive Performance in Parkinson’s Disease

Abstract: Background Sleep disturbances and impairment of cognitive function are among the most frequent non-motor symptoms in Parkinson’s disease (PD) with negative implications on quality of life of patients and caregivers. Despite the fact that sleep disturbances are a major issue in PD patients, only limited data are available regarding interactions of sleep disturbances and cognitive performance. Objective This post hoc analysis of the RaSPar trial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 68 publications
(99 reference statements)
0
18
0
Order By: Relevance
“…Of note, recent studies have demonstrated the RBD increased risk of cognitive impairment (Boot et al, 2012 ; Postuma et al, 2019 ). A recent study has reported no significant differences in cognitive performance between patients with PD-pRBD + and PD-pRBD − , whereas cognitive decline is associated with sleep efficiency (Hermann et al, 2020 ). In this work, we found that patients with PD-pRBD + exhibited a more rapid decline in cognition.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, recent studies have demonstrated the RBD increased risk of cognitive impairment (Boot et al, 2012 ; Postuma et al, 2019 ). A recent study has reported no significant differences in cognitive performance between patients with PD-pRBD + and PD-pRBD − , whereas cognitive decline is associated with sleep efficiency (Hermann et al, 2020 ). In this work, we found that patients with PD-pRBD + exhibited a more rapid decline in cognition.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that pulmonary dysfunction, rigidity of muscles of the chest wall, and changes in posture/kyphoscoliosis may be potential risks for SDB in PD patients [ 32 ]. Neurodegeneration was also proposed as a cause of SDB in PD, but studies showed no correlation between SDB and caudal brainstem serotonergic innervation or striatal dopaminergic innervation [ 140 ]. There is also an association between SDB and other types of sleep disorders.…”
Section: Sleep Disorders and Pharmacological Treatmentsmentioning
confidence: 99%
“…For example, OSA can aggravate excessive daytime somnolence in PD patients [ 141 ]. In some studies, SDB increases the frequency and severity of RBD events and RBD may render PD patients prone to SDB, although RBD influences sleep-related breathing parameters modestly [ 142 , 143 ] but in other studies, PD patients with RBD seem to experience lower rate of OSA, which is possibly due to a protective effect of enhanced muscle tone during REM sleep [ 140 ].…”
Section: Sleep Disorders and Pharmacological Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Supine sleep was related to longer disease duration, daytime sleepiness and a higher AHI but not to total sleep time, sleep efficiency or sleep stage. Additionally, an AHI > 5/h and decreased sleep efficiency have been reported to contribute to impaired cognition, particularly attention, executive function/working memory, and semantic memory in patients with PD [169], implying that the Over 11 years of follow-up in community-dwelling older men, reduced circadian rhythmicity was associated with an increased risk of incident PD [177].…”
Section: Rls With Pdmentioning
confidence: 99%